2018
DOI: 10.1016/j.ijnurstu.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of heart failure dyadic self-care interventions focusing on intervention components, contexts, and outcomes

Abstract: A B S T R A C T Background:Having support from an informal carer is important for heart failure patients. Carers have the potential to improve patient self-care. At the same time, it should be acknowledged that caregiving could affect the carer negatively and cause emotional reactions of burden and stress. Dyadic (patient and informal carer) heart failure self-care interventions seek to improve patient self-care such as adherence to medical treatment, exercise training, symptom monitoring and symptom managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
94
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 53 publications
3
94
0
7
Order By: Relevance
“…36,37 On the contrary, other showed greater risk of hospitalization associated with better self-care, suggesting that more consistent engagement in self-care behaviours is driven in part by the progressive nature of HF. 38 In fact, few studies have demonstrated a reduction in readmission rates based on HF self-care education even in a dyadic way, including the caregiver, 39,40 and the use of self-management programmes have also shown inconsistent effects on outcomes even if most of these studies enrolled patients younger than those enrolled in our cohort. 14,40,41 Also, a meta-analysis including the most relevant studies showed that self-management interventions may be less beneficial in older than in younger patients, may not benefit or even cause harm in patients with depression, or may not improve key outcomes (i.e.…”
Section: Self-care Ability and Outcomesmentioning
confidence: 91%
“…36,37 On the contrary, other showed greater risk of hospitalization associated with better self-care, suggesting that more consistent engagement in self-care behaviours is driven in part by the progressive nature of HF. 38 In fact, few studies have demonstrated a reduction in readmission rates based on HF self-care education even in a dyadic way, including the caregiver, 39,40 and the use of self-management programmes have also shown inconsistent effects on outcomes even if most of these studies enrolled patients younger than those enrolled in our cohort. 14,40,41 Also, a meta-analysis including the most relevant studies showed that self-management interventions may be less beneficial in older than in younger patients, may not benefit or even cause harm in patients with depression, or may not improve key outcomes (i.e.…”
Section: Self-care Ability and Outcomesmentioning
confidence: 91%
“…Engagement with both pulmonary and cardiac rehabilitation has demonstrated positive improvements in patient HRQoL (Casaburi, ; Sagar et al, ). Existing evidence is conflicting regarding the success of the intervention and lacks clarity about the extent of the involvement of caregivers and the methodological rigour (Bryant et al, ; Buck et al, ; Evangelista, Strӧmberg, & Dionne‐Odom, ). A review of self‐management approaches for people with chronic conditions indicates that there is a gap in the literature with regard to caregivers and self‐management interventions (Barlow, Wright, Sheasby, Turner, & Hainsworth, ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we highlight the absence of both the dyadic theoretical and review literature from this article. From a key theoretical article (cited 500+) by Berg and Upchurch in which a developmental and contextual dyadic chronic illness model was introduced to a recent international systematic review of dyadic interventions in which intervention components, contexts, and outcomes were examined, there is a rich body of work that was not brought to the attention of the readers of this article. One particular article, by Lyons and Lee, exemplifies this issue.…”
mentioning
confidence: 99%